Modeling and Hybrid Calculation Architecture for Cyber Physical Power Systems - Manli Li; Yusheng Xue; Ming Ni; Xiao Li (IEEE Access, 2020)
Traditional isolated modeling and calculation methods for cyber systems and power systems cannot satisfy the requirements for the analysis and control of cyber physical power systems (CPPSs). In this paper, a matrix-based modeling method for the coupled behavior of a CPPS is presented to describe the complex interactions of the information and energy flows. A hybrid calculation architecture is proposed for the reliability and security analysis of CPPSs. On that basis, the CPPS security defense system is established. Case studies verify the effectiveness of this CPPS modeling approach and hybrid calculation architecture.